Assessing Recent Technologies for Addressing Microplastic Pollution and Pushing the Case of Bioremediation as an Attractive Approach - Bhatt, Ekta; Gauba, Pammi; Sarethy, Indira P. (Recent Advances in Food Nutrition & Agriculture, 2025)
Microplastics are emerging sources of environmental pollutants that are increasingly of concern because of their harmful impacts on aquatic life and thereby humans. Their accumulation in the environment is in direct proportion to global plastic production; their being non-degradable, recalcitrant and of a persistent nature creates an urgent need to address this issue on a global scale. Recent reports have demonstrated the presence of microplastics in marine life, and directly becoming a part of the food chain when seafood is ingested by humans. The repercussions of these studies point to an even larger scale presence of microplastics across varied habitats, which are yet to be sampled. Bioremediation, using various microorganisms such as bacteria, algae and fungi, alone or as consortia or in biofilm form can be used as an effective remediation tool. Genetically modified microorganisms for focused removal of microplastics and metagenomics studies, providing taxonomic details of uncultured organisms, are also expected to provide an additional catalogue of technologies in this field. This review offers a comprehensive overview of microplastic sources, existing technologies for treating microplastics and an in-depth analysis of bioremediation mechanisms, its components, and the results from various studies which provide sufficient clues as to the directions to be chosen to address microplastics pollution and can facilitate and instruct researchers to further investigate the more practical approaches and create new and innovative strategies for advanced remediation of microplastic in the future.
Keywords: bioremediation